2023
DOI: 10.3390/fermentation9050449
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Substrates Used for Biogas Production in Terms of Water Content

Abstract: New technologies based on the anaerobic digestion process make it possible to manage problematic waste. Methane efficiency depends largely on the level of the hydration of the substrates used for biogas production and their ability to decompose easily. The aim of this study was to present the current state of knowledge and practices in substrate hydration characteristics, focusing on pretreatment methods as the preferred method for improving efficiency. The paper discusses issues related to the degree of hydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…In addition, it was shown in the work that already as a result of significant losses, primarily from nitrogen compounds, the composition of the digestate may be richer in these nutrients [136][137][138].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was shown in the work that already as a result of significant losses, primarily from nitrogen compounds, the composition of the digestate may be richer in these nutrients [136][137][138].…”
Section: Discussionmentioning
confidence: 99%
“…Another solution that brings measurable profits is the construction of a local biogas plant with a capacity of 250-500 kW and use of other waste streams [76,[120][121][122][123]. In the analyzed case, it would be an installation intended for a dozen local farmers (up to 10 km from the installation) and waste streams other than manure.…”
Section: Discussionmentioning
confidence: 99%
“…Biogas composition including methane, carbon dioxide, and hydrogen sulphide are demonstrated in Figure 2a-c, respectively. Methane and carbon dioxide have a major portion in biogas mixture, and the other components are present in small amounts depending on substrate characteristics, as Czekała et al [58] reported substrates with higher portions of carbohydrate and protein have a high hydrolysis rate, but substrates with fat have a comparatively high methane content in biogas. Methane contents of biogas produced from 100:0, 90:10, 70:30, 50:50, 30:70, 10:90, and 0:100 test groups were 52.78%, 51.80%, 51.68%, 51.76%, 51.25%, 51.15%, and 51.61%, respectively (Figure 2c).…”
Section: Analysis Of Biogas Compositionmentioning
confidence: 99%